Kota Cina dan Pulau Kompei: Perbandingan Temuan Arkeologis Aktivitas Perdagangan di Bandar- Bandar Pesisir Timur Sumatera - Stanov Purnawibowo (Berkala Arkeologi Sangkhakala, 2007)
AbstractTrade activities in Kota Cina and Pulau Kompei in east coast Sumatera, have a growth approximately 13 th -- 16 th Centuries. The comparison of archaeological records between Kota Cina and Pulau Kompei may gave a few conclution about growth and disappeared an anchorages.